The RENDEMEN HIDROKSIAPATIT DARI TULANG IKAN CAKALANG (Katsuwonus pelamis) DENGAN LAMA WAKTU 12, 24, 36, 48 JAM DENGAN METODE PRESIPITASI - Syamsiah Syam; Mila Febriany; Indrya Kirana Mattulda; Husnah Husein; Ilham Abbas (YARSI Dental Journal, 2026)
Background: Skipjack tuna (Katsuwonus pelamis) bone waste in South Sulawesi has high potential as a natural hydroxyapatite (HA) source due to its calcium–phosphate content. However, the effect of precipitation duration on HA yield and phase composition remains unclear. Research Objective: To evaluate the effect of precipitation time (12, 24, 36, and 48 hours) on hydroxyapatite yield and phase composition from skipjack tuna bone. Methods: Experimental laboratory study using precipitation method. Bone-derived CaO was reacted with 0.6 M H₃PO₄ under controlled pH using NaOH 1 M. The precipitate was aged for 12–48 hours, dried, calcined, and weighed to determine yield. Phase composition was analyzed using XRD. Results: The highest yield was obtained at 24 hours (97.807%). Longer durations (36 and 48 hours) reduced yield. XRD showed Whitlockite dominance at 12 hours (84.5%), increased Hydroxyapatite at 24 hours (46.1%), Whitlockite re-dominance at 36 hours (50.4%), and Fluorapatite dominance at 48 hours (49.7%). Conclusion: A 24-hour precipitation time produced the highest HA yield with balanced phase composition. Prolonged precipitation altered mineral phases and reduced efficiency.